Italian expert consensus for the management of actinic keratosis in immunocompetent patients. (6th April 2016) - Peris, K.; Calzavara‐Pinton, P.G.; Neri, L.; Girolomoni, G.; Malara, G.; Parodi, A.; Piaserico, S.; Rossi, R.; Pellacani, G.
Abstract: Actinic keratosis (AK) is a common skin disease which can potentially progress to invasive squamous cell carcinoma (iSCC). Given that mortality rates and health‐care cost associated with iSCC are substantial, the management of AK represents an important public health issue. Several effective lesion‐directed and field‐directed treatments are available. Ablative procedures (e.g. cryosurgery, excision, laser ablation, curettage alone or with electrodessication) are considered cost‐effective options for solitary lesions. Field‐directed therapies (e.g. Ingenol Mebutate, imiquimod, PDT, 5‐Fluorouracile, diclofenac 3%, 5‐FU + Salicylic acid) can be used over large epidermal surfaces and are directed to treat both individual visible lesions and cancerization fields. In order to provide guidance for management choice in clinical practice, several guidelines concerning the diagnosis and treatment of AK have been published in the past decade. However, the introduction of novel therapeutic options requires continuous updates of recommendations and adaptation to national contexts. The present review summarizes the existing evidence and reports the results of a consensus workshop on the management of AK.